PENYUSUNAN LAPORAN KEUANGAN TAHUN 2014 PADA RUMAH SAKIT BERSTATUS BLUD DENGAN SAK ETAP (Studi Kasus Pada Rumah Sakit â€œXâ€) - Noorrochmah, Irene Anggiat; Adam, Helmy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The hospital is a unit of services that provide social services in health care. Hospital management unit has unique because in addition to being a service unit, operation of hospitals also have a social mission. Changes in the status of RSUP to BLUD cause changes standards used to prepare financial statements. BLUD given the flexibility of financial management based on the principles of economic, productivity and the application of good business practice.Â It is therefore expected that the status BLUD hospital is able to present financial statements in accordance with standards set by the government that the Financial Accounting Standards Entities Without Public Accountability (SAK ETAP). In the presentation of financial statements Hospital using government accounting standards (SAP) that is not accordance with PP 23, 2005, article 26, which recommends accounting and financial statements BLUD held in accordance with Financial Accounting Standards (IFRSs) issued by the Indonesian Institute of Accountants (IAI). Therefore, researchers presenting the financial statements and accounting policies conform's standards specified. This study was conducted at Hospital Dr. â€œXâ€ hospital is one of the advanced level BLUD status. The analysis used isis used descriptive analysis. The results in this study shows that the financial statements are in stacking by the Hospital Dr. â€œXâ€ has not fully implemented the financial accounting standards entities without public accountability (SAK ETAP) and it is because of the limited knowledge of its human resources, as well as the previous system has been running very well established, making it difficult to change to a new system, nothing socialization about SAK.